Komunikasi Pelayanan Publik di Bidang Kesehatan: Studi pada Rumah Sakit Universitas Sumatera Utara - Pohan , Syafruddin; Urrahmah, Syifa; Ginting, Teria S (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This study aims to examine the quality of public services in the health sector and their impact on patient satisfaction at the Prof.dr. Panusunan Lubis Hospital, University of North Sumatra (USU Hospital). In this study, a qualitative approach with descriptive method was used. Data were collected through interviews with four patients who are currently or have undergone treatment at USU Hospital. The results showed that most patients were satisfied with the quality of service they received at USU Hospital. Factors such as reliability, responsiveness, assurance, empathy, and physical evidence have contributed positively to the patient experience. However, there were some complaints from some patients related to unfriendly administrative services, incompetent nurses, and room mismatches with expectations. In conclusion, good public service quality at USU Hospital has increased patient satisfaction, although there are still some areas that need to be improved. The results of this study can be valuable input for USU Hospital in improving public services and patient experience to achieve higher standards. Keyword: Quality of Public Service, Patient Satisfaction, Prof. Dr. Panusunan Lubis Sumatera Utara University Hospital